Evaluation of a population health strategy to reduce distracted driving: Examining all "Es" of injury prevention. Issue 3 (24th March 2021) - Charyk Stewart, Tanya; Edwards, Jane; Penney, Alyssa; Gilliland, Jason; Clark, Andrew; Haidar, Tania; Batey, Brandon; Pfeffer, Amanda; Fraser, Douglas D.; Merritt, Neil H.; Parry, Neil G.
Abstract : BACKGROUND: Cell phone use while driving (CPWD) increases the risk of crashing and is a major contributor to injuries and deaths. The objective of this study was to describe the evaluation of a multifaceted, evidence-based population health strategy for the reduction of distracted driving. METHODS: A multipronged campaign was undertaken from 2014 to 2016 for 16- to 44-year-olds, based on epidemiology, focused on personal stories and consequences, using the "Es" of injury prevention (epidemiology, education, environment, enforcement, and evaluation). Education consisted of distracted driving videos, informational cards, a social media AdTube campaign, and a movie theater trailer, which were evaluated with a questionnaire regarding CPWD attitudes, opinions, and behaviors. Spatial analysis of data within a geographic information system was used to target advertisements. A random sample telephone survey evaluated public awareness of the campaign. Increased CPWD enforcement was undertaken by police services and evaluated by ARIMA time series modeling. RESULTS: The AdTube campaign had a view rate of >10% (41, 101 views), slightly higher for females. The top performing age group was 18- to 24-year-olds (49%). Our survey found 61% of respondents used handheld CPWD (14% all of the time) with 80% reporting our movie trailer made them think twice about future CPWD. A stakeholder survey and spatial analysis targeted our advertisements in areas of close proximity to high schools, universities, near intersections with previous motor vehicle collisions, high traffic volumes, and population density. A telephone survey revealed that 41% of the respondents were aware of our campaign, 17% from our print and movie theater ads and 3% from social media. Police enforcement campaign blitzes resulted in 160 tickets for CPWD. Following campaign implementation, there was a statistically significant mean decrease of 462 distracted driving citations annually ( p = 0.001). CONCLUSION: A multifaceted, evidence-based population health strategy using the Es of injury prevention with interdisciplinary collaboration is a comprehensive method to be used for the reduction of distracted driving. LEVEL OF EVIDENCE: Therapeutic, level IV.